Acts of state and the frontiers of private (international) law - Dickinson, A (Taylor and Francis, 2018)
A growing number of cases before the English courts implicate governmental or sovereign acts with a foreign connection. Cases involving “acts of state” have in the past been bedeviled by legal uncertainty, in terms both of the rationalisation of the common law’s approach to them, and the relationship of the rules and principles deployed to the private international law rules ordinarily applied in cases with a cross-border aspect. Three recent decisions of the Supreme Court offer some valuable insights, and a welcome opportunity to take stock and to re-consider the account in the leading modern English commentary.